Effect of Cherry Extract and Almond Oil on Oxonic cid-Induced Hyperuricemia in Male Albino Rats - J. Khdhir , Chrakhan; H. Hussein, Ridha; A. Azeez , Hoshyar (Al-Nahrain Journal of Science, 2019)
This study designed to investigate the effects of cherry extraction, almond oil, and their combination on physiological and some biochemical parameters in oxonic acid-induced hyperuricemic rats. Hyperuricemia was induced experimentally by intraperitoneal injection of rats with oxonic acid (OA) (250mg/kg/bw) daily for two weeks. The animals were randomly divided into six groups each included six rats: normal control, Hyperuricemic (HU), HU+ Allopurinolas a positive control (AP)(5mg/kg/bw), HU+ Cherry extract (500mg/kg/bw), HU+ Almond oil (3ml/kg/bw), and HU+ co-treatment of (Cherry extract+ Almond oil). The treatments were administrated orally by intragastric tube (gavage) 1 h after OA injection daily throughout the study.At the end of the experiment, the rats were fasted overnight, anesthetized then blood samples were collected for biochemical analysis and detection of oxidative stress.Results indicated that injection with OA induced hyperuricemia after two weeks in rats by increasing the level of serum uric acid significantly (P≤0.0001),and a significantelevation in the levels of BUN, SCr, XO, and LPO were observed, whereas the level of serum SOD decreased.Moreover, treatment with HU rats with AP, cherry extract and almond oil alone and in their combination group, all significantly decreased SUA, SCr, BUN (except for the almond oil group in which Scr and BUN decreased non-significantly)and reversing the results of oxidative stress. Finally, the results showed that the effects of combined treatment (cherry extract + almond oil) was near the actions of allopurinol.